Principle of Bifocal Antennas Implemented in a Dual Reflectarray Configuration - Cuevas Castillo, Jesus Gustavo; Herrero, C. Tienda; Encinar, Jose Antonio; Krieger, Gerhard (European Conference on Antennas and Propagation (EuCAP), 2015)
A procedure to compute the phase distribution on dual reflectarray antennas applying the principle of bifocal antennas is proposed. Two different approaches have been used for centered and offset configurations. The design methods have been applied to synthesize the phase distribution of two dual reflectarray antennas working in Ka-band
DLR Import::2019-04-03